Assessment of the Nutritional Content and Hedonic Test on Pameling Avocado from Three Different Altitudes - Permanasari, Paramyta Nila; Karyawati, Anna Satyana; Saitama, Akbar; Wicaksono, Karuniawan Puji (International Journal of Environment, Agriculture and Biotechnology, 2023)
Malang Regency has superior avocado commodity which is so-called Pameling. Superiorities of the fruit are indicated by the large size of the fruit and quality of the fruit flesh which is liked by the consumers. Today, the development of Pameling avocado has expanded from the lowlands to the highlands in diverse regions. In order to obtain optimal harvest yields, both quantity and quality, the research affirmed the quality of Pameling avocado, which is grown at the lowlands and the highlands. The research was conducted by testing quality (nutritional content) and organoleptic. Results of the research showed that the avocados grown at the highlands were more preferred by the panelists based on the organoleptic test from the assessment aspects of appearance, texture, aroma, and taste. The lowlands produced preference of the color flesh which is mostly preferred by the panelists. Results of the nutritional test (quality) on fruits grown at the lowlands showed the highest level of sugar and protein. The middle plains are superior in fat content. Moreover, the highlands produce fruits with the highest coarse fibers. However, the differences in cultivation methods on three different altitudes will be the subject of further studies that need to be considered.